CUSTOMER SATISFACTION AND TRUST TOWARDS CASHLESS TRANSACTIONS - Anandhi, G.; Bastin Jerome, V. (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to find the customer satisfaction and trust towards cashless transactions in Tiruchirappalli City. In the field of digital payment systems, there are very few researches on customer satisfaction with cashless transaction systems. This exploratory research is the first to test consumer satisfaction level towards cashless transaction systems through providing digital payment platform. The primary objective of the current research study is to customer satisfaction with cashless transaction systems in Tiruchirappalli through survey method. Adoption of cashless payment systems can help society in the development of the economy. Cashless payment system providers focus not only on the adoption of cashless payment systems but also the satisfaction of the consumers in Tiruchirappalli City. The objective of this study is to understand customer satisfaction with cashless transaction systems in Tiruchirappalli City and also to understand consumers usage related to cashless transactions. The current study has used survey method for collecting primary data of 500 respondents using convenience sampling technique for the empirical analysis of consumers’ attitude towards doing cashless transactions.